Effects of the hydrothermal liquefaction aqueous phase on activated sludge - Blackwell, Shelley M.; Crowe, Braden J.; Brady, Colin; Schmidt, Andrew J.; Walker, John H.; Benemann, John R.; Lundquist, Tryg J. (Frontiers in Chemical Engineering, 2025)
Hydrothermal liquefaction (HTL) is a developing alternative for municipal wastewater sludge management that converts sludge into biocrude oil that can be refined into a liquid transportation fuel for the road, marine, and aviation sectors. A major byproduct of HTL is an aqueous phase (AP) high in ammonia, organic carbon, and potentially toxic compounds. This study investigated the feasibility of disposing AP through discharge into the headworks of conventional activated sludge water resource recovery facilities (WRRFs). Bench-scale, acute inhibition experiments using non-nitrifying mixed liquor indicated that a single AP exposure did not inhibit the specific oxygen uptake rates (SOUR) at pilot- and full-scale dilutions (0.03%–0.4% v/v). In contrast, post-secondary nitrifying mixed liquor showed that SOUR inhibition was linearly correlated to the AP concentration. Chronic AP exposure studies (121 days of operation) in continuous-flow, 2.25-L, non-nitrifying activated sludge reactors also indicated that SOUR was unaffected at the pilot- and full-scale AP dilutions in synthetic wastewater feed. However, repeated-measure linear-mixed models showed statistically significant lower specific dissolved organic carbon (DOC) removal rates and percentage DOC removal associated with higher AP concentration in the influent. At the full-scale AP concentration, removal rates were 25 mg DOC/g TSS-hr less and mean percent DOC removal was 40% lower than controls, despite higher DOC loading to the +AP reactors. Furthermore, ultraviolet transmittance (UVT) in the effluent of these reactors was 93% less than in the controls. The results of this study suggest that while headworks discharge of AP at pilot scale might be feasible, full-scale would require pretreatment of the AP, especially at WRRFs that use ultraviolet disinfection. The lack of detectable inhibition in non-nitrifying activated sludge via batch SOUR tests contrasted with the reduction in DOC removal detected in the continuous reactor studies. This result indicates the value of continuous studies to adequately understand the implications of AP headworks discharge on activated sludge processes. To our knowledge, this study is the first to characterize the effects of chronic exposure of mixed liquor to AP in continuous-flow activated sludge reactors.